Human Action, Economics, and Ethics - Aranzadi, Javier (SpringerBriefs in Economics,, 2018)
In the economical changing and political disturbing times we are living a question concerns us all: Is this the society I want to live in? What are the opportunities I have to pursue in my socio-cultural environment? Which echoes the ancient Greek ethical questions: What is the best city to live in? What do I want to do with my live? In this book the author goes back to the primary reality of our lives: human action. From the analysis of the anthropological elements of human action -culture, society, individual action- the book will help the reader to understand the construction of our economic reality and how to approach the perennial ethical question: How can I develop excellence in my life?